CLINICAL RELATIONSHIP BETWEEN NONSPECIFIC AND SPECIFIC SYMPTOMS IN NON-PSYCHOTIC MORBIDITY - Srinivasan, T.N. (Medknow Publications, 1989)
The phenomenon of non-specific somatic symptom presentation by patients with non-psychotic mental morbidity attending primary care clinics is a well recorded one. The nature of clinical relationship of these symptoms to specific psychiatric phenomena was studied in a group of non-psychotic patients attending a primary care general hospital clinic. It was seen that both types of symptoms occur with equal frequency in these patients. It appears that non-specific symptoms are a preferred mode of presentation of this category of patients rather than the possibility that they totally ‘mask’ or predominate more than specific psychiatric phenomena.